The Role of Organizational Agility in Mediating the Effect of AI-Driven Human Resource Management and ESG Practices on Business Sustainability in the Telecommunications Industry - Ganjar Garibaldi; Joelianti Dwi Supraptiningsih; Pristanto Ria Irawan (Global Research Collaboration, 2026)
The growing convergence of digital transformation and sustainability governance has intensified organizational pressure to achieve long-term competitiveness while responding to technological disruption, environmental uncertainty, and stakeholder expectations. Although AI-driven organizational systems and ESG-oriented practices are widely promoted as strategic drivers of sustainable performance, empirical findings regarding their effectiveness remain inconsistent across organizational contexts. This study addresses this theoretical and empirical inconsistency by examining the role of Organizational Agility as a strategic mechanism linking AI-Driven Human Resource Management (AI-Driven HRM) and ESG Practices to Business Sustainability within the telecommunications industry. Drawing upon Dynamic Capability Theory, the study challenges deterministic assumptions suggesting that technological adoption and sustainability governance automatically generate sustainable organizational outcomes. A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 150 employees working in telecommunications companies in Jakarta, Indonesia, through purposive sampling and structured questionnaire distribution. The findings reveal that ESG Practices significantly enhance Organizational Agility, while Organizational Agility substantially strengthens Business Sustainability. Conversely, AI-Driven HRM does not significantly influence Organizational Agility or Business Sustainability directly, indicating the existence of an organizational capability gap within digital transformation processes. Furthermore, Organizational Agility significantly mediates the relationship between ESG Practices and Business Sustainability, whereas its mediating role in the relationship between AI-Driven HRM and Business Sustainability is not statistically significant. These findings demonstrate that sustainable organizational performance is shaped less by technological implementation itself and more by the organization’s adaptive capability to transform sustainability-oriented governance into responsive strategic behavior. The study contributes theoretically by extending Dynamic Capability Theory through a capability-based sustainability perspective that positions Organizational Agility as a strategic conversion mechanism within digitally transforming organizations. Practically, the findings provide strategic insights for organizations seeking to strengthen sustainable competitiveness in increasingly volatile and technology-driven business environments.